The program : lessons from elite military units for creating and sustaining high performance leaders and teams - Kapitulik, Eric; MacDonald, Jake (Marine Corps officer) (John Wiley & Sons, Inc., 2019)
"Active business capitalizes on popular motivational category: The Program combines military experience and motivation like popular books Make Your Bed, The Way of the SEAL, Team of Teams, and Extreme Ownership among many others. Author Plan for Moving Books Through Speaking Engagements and Keynotes: Eric Kapitulik and his team of distinguished, retired military veterans and former varsity athletes speak in front of approximately 150 sports teams and departments and corporations a year. He will either give the book to attendees or drive sales to retail around these events. PR:Eric Kapitulik will hire a marketing firm at publication to promote the book. The company has a database of close to 10,000 prospects and clients who can't afford to work with them, but continuously ask about a book as a more cost-effective way of learning The Program. Kapitulik participates in athletic and corporate podcasts with audiences totaling more than 400,000 listeners. ESPN correspondent Marty Smith who has a weekly TV show, podcast and twitter following of more than 250,000 has already agreed to feature the author on all three"--